Locating the influencer : place and platform in global tourism - Ritter, Christian S. (Emerald Publishing Limited, 2024)
The ubiquity of digital platforms in everyday life has considerable ramifications for contemporary leisure travel. Drawing on a long-term ethnographic investigation into the trials and tribulations of travel influencers, Locating the Influencer provides an account of the emergence of a new professional group in global tourism. Christian S. Ritter assesses the transformative role of travel vlogs in the mediation of tourist places using in-depth interviews, participant observation and network visualisations. In following journeys to European and Southeast Asian destinations, the travel ethnography depicts the spirit of adventure, mobile lifestyles, video-making practices and encounters with local tourism professionals. Locating the Influencer reveals how travel influencers build their professional expertise and engage in collaborations with local destination stakeholders, monetise their travel content, maintain parasocial relationships with large audiences, and the employ tactics to deal with algorithms. Amid climate disasters inducing lasting debates about both the future of tourism and sustainable tourism, Locating the Influencer comprehensively investigates the digital phenomenon of the travel influencer and offers a way to trace the polyvocal voices of platform-nested storytelling in global tourism.
Keywords: Tourism -- Technological innovations.; Travel -- Social aspects.; Internet personalities.; Tourism -- Information technology.; Social Science -- Media Studies.; Media studies: internet, digital media and society.; Media studies.; elektronické knihy; electronic books